1985
DOI: 10.1161/01.str.16.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis--a review of 38 cases.

Abstract: 199SUMMARY A series of 38 patients with angiographically proven cerebral venous thrombosis (CVT) affecting dural sinuses is reported. This study shows that CVT is not rare, that the clinical diagnosis is extremely difficult because of the variable modes of onset and groupings of symptoms, that most CT findings are non specific and that angiography remains the best diagnostic tool. Only 4 patients died, which suggests a more benign outcome than classically described. None of the 23 heparin treated patients died… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
426
3
34

Year Published

1986
1986
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 685 publications
(468 citation statements)
references
References 57 publications
5
426
3
34
Order By: Relevance
“…The occurrence of astrogliosis in the current study could be explained by a decrease in cerebral perfusion [8,37] and decreased regional cerebral oxygen saturation [46]. In another study, Román et al [36] revealed that gliosis was detected in the brain after incomplete ischemic injuries.…”
supporting
confidence: 47%
“…The occurrence of astrogliosis in the current study could be explained by a decrease in cerebral perfusion [8,37] and decreased regional cerebral oxygen saturation [46]. In another study, Román et al [36] revealed that gliosis was detected in the brain after incomplete ischemic injuries.…”
supporting
confidence: 47%
“…Headache is the presenting symptom in 70-90% of cases. [20,21,22] Focal deficits such as hemiparesis and hemisensory disturbance, seizures, impairment of level of consciousness and papilloedema occur in onethird to three-quarters of cases. [20,22] The onset may be acute, subacute or insidious, most patients presenting with symptoms which have evolved over days or weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[20,21,22] Focal deficits such as hemiparesis and hemisensory disturbance, seizures, impairment of level of consciousness and papilloedema occur in onethird to three-quarters of cases. [20,22] The onset may be acute, subacute or insidious, most patients presenting with symptoms which have evolved over days or weeks. [20] There are several typical clinical constellations [21,23] : 18-38% of cases present with a syndrome resembling benign intracranial hypertension with headache, papilloedema and visual disturbances; up to 75% of cases are characterised by a focal neurological deficit andheadache; a third group of between 30% and 50% may present with seizures often followed by a Todd's paresis.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely to be lower than the incidence of approximately 1 per 1000 persons per year reported for deep-vein thrombosis. In 61% of affected women, intracerebral venous thrombosis occurs between the ages 20 and 35 years, which coincides with peak oral contraceptive use and incidence of pregnancy [2,3,11]. Using oral contraceptives is a well-known risk factor for CVT.…”
Section: Discussionmentioning
confidence: 99%